Evaluating agroforestry patterns to increase land productivity of Falcataria moluccana private forests in Central Lombok Regency, West Nusa Tenggara - Nandini, Ryke; Susila, I Wayan Widhana; Agustarini, Retno; Samawandana, Gipi (Forestry Faculty, Universitas Hasanuddin, 2023)
Developing agroforestry systems in private forests is expected to increase productivity. This study aims to determine the appropriate agroforestry design for Falcataria moluccana-based private forests in Central Lombok Regency. Three intercrop species were tested: small taro (Colocasia esculenta), ginger (Zingiber officinale), and vanilla (Vanilla planifolia Andrews). This study was established using a completely randomized design. The three planting combinations were examined in three replications for a total of nine test plots: F. moluccana+vanilla+small taro (FmVT), F. moluccana+vanilla+ginger (FmVG), and F. moluccana+vanilla+ginger+small taro (FmVGT). Each test plot was 10 x 10 m and was located at 3 x 3 m spacing under a 3-year-old F. moluccana stand. The measured variables were crop survival rates, plant yields, and microclimatic data. The correlation between the variables was examined using the Pearson Product Moment, Duncan's advanced multiple range test (DMRT), and analysis of variance (ANOVA). The market price was used to determine the crop's economic value. The best agroforestry design was based on the economic value of crop production and the land equivalent ratio. The results indicated that the combination of F. moluccana, vanilla, ginger, and small taro, which generated an additional income of IDR 11,851,250 ha-1 a year, should be widely promoted and adopted.